2017
DOI: 10.1080/17434440.2018.1419060
|View full text |Cite
|
Sign up to set email alerts
|

XEN Gel Implant: a new surgical approach in glaucoma

Abstract: Glaucoma is a leading cause of blindness worldwide. Intraocular pressure (IOP) lowering is the only effective treatment strategy. Traditional glaucoma surgeries are generally considered to be unpredictable and associated with a high rate of complications. This has led to the development of a novel XEN Gel Implant, a type of minimally invasive glaucoma surgery (MIGS), lowering the IOP without extensive surgical dissection. Areas covered: A literature search was undertaken on PubMed using the terms XEN glaucoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 59 publications
2
62
1
15
Order By: Relevance
“…In the absence of a standard protocol for bleb management, a variety of interventions have been used postoperatively, including reintroduction of antiglaucoma medications in case of IOP increase. The needling rate with the XEN Gel Stent varies widely, [15] from\ 3% with MMC [16,17] to approximately 50% when performed without antimetabolites [18] or with MMC in a few cases [3]. A recent retrospective study reported that needling with 5-FU after XEN implantation resulted in a substantial IOP-lowering effect (preneedling IOP of 26.2 ± 9.5 mmHg and postneedling IOP at last follow-up of 15.4 ± 3.7 mmHg) [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of a standard protocol for bleb management, a variety of interventions have been used postoperatively, including reintroduction of antiglaucoma medications in case of IOP increase. The needling rate with the XEN Gel Stent varies widely, [15] from\ 3% with MMC [16,17] to approximately 50% when performed without antimetabolites [18] or with MMC in a few cases [3]. A recent retrospective study reported that needling with 5-FU after XEN implantation resulted in a substantial IOP-lowering effect (preneedling IOP of 26.2 ± 9.5 mmHg and postneedling IOP at last follow-up of 15.4 ± 3.7 mmHg) [19].…”
Section: Discussionmentioning
confidence: 99%
“…It consists of a 6 mm long flexible tube with a 45 μm diameter lumen made of porcine cross-linked collagen. The device is based on the principles set in the Hagen-Poiseuille equation, establishing that a longer thinner tube will provide more resistance to flow than a shorter and wider one [21].…”
Section: Xen 45 Gel Stentmentioning
confidence: 99%
“…On the other hand, in eyes with XEN implantation there is minimal manipulation of subconjunctival and episcleral tissues and therefore may require needling in the immediate postoperative period. The cause of high IOP on day 1 after surgery has been postulated to be due to blockage of the XEN implant by Tenon, blood, or exudates but has not been studied in detail [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive glaucoma surgeries (MIGS) aim to provide a safer and less-invasive alternative to incisional glaucoma surgeries for the control of intraocular pressure (IOP) [1,2]. At present, the XEN gel implant (Allergan, Dublin, CA) is the only Food and Drug Administration (FDA)-approved MIGS device that drains into the subconjunctival space and results in a bleb formation.…”
Section: Introductionmentioning
confidence: 99%